Increasing the economic efficiency of the work of Gazprom Transgaz Kazan LLC when operating gas heaters at gas distribution stations using a power supply unit - M. O. Shalnev; Ya. V. Denisova; A. F. Battalov (Омский научный вестник)
This article discusses one of the ways to increase the economic efficiency of the Gazprom Transgaz Kazan Limited Liability Company (Gazprom Transgaz Kazan LLC) in the operation of gas heaters at a gas distribution station by replacing the gas heating unit. The advantages of the equipment «ISTOK-60» over PTPG-30 are described, the calculation of the economic effect from the introduction of new equipment is given. The object of the study is the process of operating gas heaters at the gas distribution station of OOO Gazprom Transgaz Kazan, the subject is a method for increasing the economic efficiency of gas heaters. As a result of the study, the expediency of replacing old equipment with new one is proved and the economic effect is calculated. The article also raises questions about the possibility of using the concept of «Lean production» in the process of gas distribution. One of the methods of lean manufacturing — SMED is proposed as the main one.